The Effect of Receivable Turnover, Current Ratio, and Debt to Asset Ratio to Return on Asset in Subsector Companies Retails Registered at the Indonesia Stock Exchange Period 2018-2022 - Dedie Gunawan; Pujiarti Pujiarti (Komunitas Dosen Indonesia, 2023)
Making a profit, boosting corporate value, and expanding their business are the same objectives shared by service businesses, trading firms, and manufacturing firms. Entrepreneurs must be able to win the competition by meeting business needs, enhancing management effectiveness, and developing strategies in the rapidly expanding digital era where business competition is becoming more intense. This is necessary for their own survival as well as the survival of the business. Purposive sampling, which uses a sampling procedure with specific considerations, was the strategy utilized to choose the sample for this research. The study's findings demonstrate that accounts receivable turnover has a yield of 5.097 > 2.052 and a significant level of 0.00 < 0.05, indicating that it has a partial positive and significant impact on return on assets; the current ratio has a result of -1.691 < 2.025 and a significant level of 0.0103 > 0.05, indicating that it has a partial negative and significant impact on return on assets; and the debt to asset ratio has a result of Receivable Turnover, Current Ratio, and Debt to Asset Ratio all exhibit results of 0.000 < 0.05, suggesting simultaneous significant effects on the dependent variable from all independent factors.